1967
DOI: 10.1136/hrt.29.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Phonocardiogram of the ball-and-cage aortic valve prosthesis.

Abstract: The ball-and-cage aortic prosthesis consists of a silastic ball, which has a specific gravity of 1 1499 (S.G. of blood=1 050), enclosed within a metal cage (Starr and Edwards, 1961). The sounds produced by the ball during its movement about the cage are very characteristic and easily recognized, because they are of high frequency, short duration, and great amplitude. We have studied the phonocardiogram in patients whose aortic valves were replaced by ball-and-cage prostheses, in order to elucidate the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

1970
1970
1977
1977

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Cine studies of ball valve motion with a pulse simulator have shown bouncing or vibrating of the ball (Dayem and Raftery, 1966b), resulting in the production of such clicks. In patients with Starr-Edwards prosthetic aortic valves with non-metal (silastic) poppets, 2 or 3 systolic clicks of low intensity have been recorded in contrast to the high intensity multiple ejection clicks recorded from Starr-Edwards prosthetic valves with metal poppets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cine studies of ball valve motion with a pulse simulator have shown bouncing or vibrating of the ball (Dayem and Raftery, 1966b), resulting in the production of such clicks. In patients with Starr-Edwards prosthetic aortic valves with non-metal (silastic) poppets, 2 or 3 systolic clicks of low intensity have been recorded in contrast to the high intensity multiple ejection clicks recorded from Starr-Edwards prosthetic valves with metal poppets.…”
Section: Discussionmentioning
confidence: 99%
“…Reports by Dayem and Raftery (1966b) show that the poppet strikes the apex of the cage in early systole, and then collides randomly against the struts of the cage. There is some variability of this motion depending upon ejection velocity and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…The early systolic sound from the prosthesis Al is due to the ball impinging on the apex of the cage [5]. It is delayed relative to the onset of left ventricular ejection by the time necessary for the ball to travel from one end of the cage to the other, the ball travel time.…”
Section: Methodsmentioning
confidence: 99%
“…It is delayed relative to the onset of left ventricular ejection by the time necessary for the ball to travel from one end of the cage to the other, the ball travel time. The late systolic sound A2 is due to the ball returning to the ring [5] and coincides exactly with the end of left ventricular ejection. The ball travel time was easily calculated by substracting the A1-A2 interval from the left ventricular ejection time, and thus delays introduced by the recording systems were avoided.…”
Section: Methodsmentioning
confidence: 99%
“…Τό φαινόμενον τούτο παρετηρήθη εις 2 ασθενείς μας εκ τών οποίων ό εις κατέληξεν έν μέσω φαινομένων οξείας καρδιακής ανεπαρκείας και ή παθολογοανατομική έξέτασις τούτου άπέδειξεν άπόσπασιν τής προσθετικής βαλβΐδος έκ τής θέσεως της, ό δέ έτερος κατά τον χρόνον τής εξετάσεως ευρίσκετο εις βαρεΐαν καρδιακήν άνεπάρκειαν. βραχεΐαν τήν εν λόγω περίοδον ό ήχος διανοίξεως τής αορτικής βαλβΐδος δυνατόν να μήν είναι ακουστός λόγφ ελαττώσεως του όγκου παλμού 53 . Το φαινόμενον τοΰτο συμβαίνει και επί φυσιολογικής βαλβϊδος παρουσία κολπικής μαρμαρυγής, εις δέ τήν ήμετέραν έργασίαν παρετηρήθη εις 2 πε ριπτώσεις.…”
Section: διπλή άντικατάστασις αορτής και μιτροειδούςunclassified